Para além dos muros do manicômio : a atenção aos idosos nos Centros de Atenção Psicossocial – CAPS - Alves, Vanessa Castro (2015)
Population aging is a global phenomenon which has been producing needs and social demands, requiring a new look at the elderly and appropriate policy responses of the state and society. In this context, it is imperative that they be made adjustments in work processes and forms of management of health services, given the complex demands and needs of this population. This study presents the research developed during the course of the Master in Social Work in Graduate PUCRS Program, which had as main objective to analyze how the attention to the elderly with mental disorder is developed in community mental health services - PCC in the city of Porto Alegre, Rio Grande do Sul in order to contribute to the qualification of attention to this segment. The research is qualitative in nature and guided by the dialectical-critical framework, based on all categories, historicity and contradiction. The explanatory categories of reality were elected: Aging, Mental Health and Psychosocial Rehabilitation. Data collection was performed in 6 mental health services in the city of Porto Alegre, which were interviewed, six professional and five elderly users, totaling 11 participants. The sample selection criteria were: users aged 60 or older, of both sexes, in attendance at PCC and with enough cognitive ability to answer the questions, according to professional indication responsible for monitoring and professionals working the technical teams of PCC with higher education. The investigative proposal was submitted to the Scientific Committee of the School of Social Service, the Ethics Committee of the same University and the other Ethics Committees of the institutions partakers. The technique used for collecting data was the semi-structured interviews and data were subjected to content analysis. From the data analysis, it was found that the main demands of care presented by the elderly in PCC are related to depressive disorders, dementias, schizophrenia and affective disorders. None of the surveyed PCC provides training to staff of professionals, specific to the development of the work with the elderly. The study revealed difficulties in relation to the effectiveness of principles such as fairness and integrity in elder care in PCC, since none of the services investigated develops activities directed specifically to the elderly. It was evident that the Psychosocial Rehabilitation processes developed by PCC occur through Singular Therapeutic Project, which is developed according to the unique needs of each user. These processes have generated positive results in the lives of elderly's.